STUDENTS’ ENGAGEMENT IN ENGLISH FOR SPECIFIC PURPOSES (ESP) GROUP DISCUSSIONS: A CASE STUDY AT A UNIVERISTY - Barella, Yusawinur; Safitri, Isnaini Nur; Asri, Anindhiasti Ayu Kusuma (STKIP Persada Khatulistiwa Sintang, 2024)
English for Specific Purposes (ESP) constitutes a pedagogical approach to English language acquisition. It provides students by learning language in a certain context. Studies on implementing group discussion have been done, but not focusing on their engagement. Thus, this study investigates student engagement in English for Specific Purposes (ESP) group discussions at a university level. ESP courses are designed to meet the specific language needs of students in professional or academic contexts, enhancing their communication skills relevant to their fields. The research employs a qualitative methodology, utilizing thematic analysis to explore students' experiences and perspectives. Data were collected through classroom observations and interviews with eight undergraduate students from two higher education institutions in Indonesia. The findings reveal that group discussions in ESP classes significantly enhance students' oral communication skills, teamwork, and problem-solving abilities. However, challenges such as unequal participation and language anxiety were also identified. The study underscores the importance of effective moderation and structured discussions to ensure equitable participation and maximize engagement. These insights have practical implications for improving instructional strategies in ESP courses, ultimately fostering a more engaging and effective learning environment.Keywords: English for Specific Purposes, group discussion, students’ engagement